PUNIA DALAM TEKS PEPARIKAN NILACANDRA - Widiantana, I Kadek; Indrayani, A.A. Diah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Punia is one of the dharma paths taken by Hindus. However, the phenomena that occur in society, punia tends to things that are material in nature. So that it narrows the essence of the punia itself. In this regard, one of the literary works that discusses the nature of punia is nilacandra peparik. This research is a qualitative research. The type of data used in this research is qualitative data with the literature study method. In the nilacandra peparik text, there are 4 essence of punia that should be carried out. Punia is based on ability, punia given is based on sincerity without expecting results, punia is not merely material.